Relevance of Phosphorylation and Truncation of Tau to the Etiopathogenesis of Alzheimer’s Disease - Zhou, Yan; Shi, Jianhua; Chu, Dandan; Hu, Wen; Guan, Zongyu; Gong, Cheng-Xin; Iqbal, Khalid; Liu, Fei (Frontiers in Aging Neuroscience, 2018)
Microtubule associated protein tau is abnor¬mally hyperphosphorylated and aggregated into paired helical filaments (PHFs), which manifest as neurofibril¬lary tangles (NFTs) in the brains of individuals with Alzheimer’s disease (AD) and related tauopathies. Hyperphosphorylation and truncation of tau have been linked to the progression of the disease. However, the nature of phosphorylation and truncation of tau in AD brain are not very clear. In the present study we investigated the association of phosphorylation and truncation with high-molecular weight oligomers of tau (HMW-tau) in post-mortem AD brain by western blots. We found that tau from AD brain appears as a smear from low molecular weight (LMW) to HMW tau species in western blots developed with pan-tau antibodies. Similar level of LMW-tau was found in AD and control brains, whereas HMW-tau was found in AD brain only. HMW-tau was hyperphosphorylated at multiple sites and not unphosphorylated at Ser46 or Ser198/199/202. HMW-tau was weakly labeled by tau antibodies 43D against a.a. 6-18 and HT7 against a.a. 159-163 of tau, whereas, the C-terminal antibodies, tau46 and tau46.1, strongly labeled HMW-tau. The ratio of HMW-tau/LMW-tau detected by tau antibodies increased as the epitope of the tau antibodies ranges from N-terminal to C-terminal. The level of tau truncated at Asp421 was increased in AD brain, but was poorly associated with the HMW-tau. These findings suggest that tau pathogenesis involves both hyperphosphorylation and dominantly N-terminal truncation of tau in AD.